2002
DOI: 10.1007/pl00001265
|View full text |Cite
|
Sign up to set email alerts
|

Using Automated, High-precision Repicking to Improve Delineation of Microseismic Structures at the Soultz Geothermal Reservoir

Abstract: Ð An automatic, adaptive, correlation-based algorithm for adjusting phase picks in large digital seismic data sets provides signi®cant improvement in resolution of microseismic structures using only a small fraction of the time and manpower which would be required to re-analyze waveforms manually or semi-automatically. We apply this technique to induced seismicity at the Soultz-sous-Foreà ts geothermal site, France. The method is ®rst applied to a small, previously manually repicked subset of the catalogue so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…This makes the method robust in the presence of electronic noise by only saving time lags when the two signals are sufficiently similar to warrant doing so. This is similar to the coherency‐based filtering technique described by Rowe et al [2002].…”
Section: Interstation Arrival Times: Vertical Componentsmentioning
confidence: 83%
See 1 more Smart Citation
“…This makes the method robust in the presence of electronic noise by only saving time lags when the two signals are sufficiently similar to warrant doing so. This is similar to the coherency‐based filtering technique described by Rowe et al [2002].…”
Section: Interstation Arrival Times: Vertical Componentsmentioning
confidence: 83%
“…In the cross‐spectral technique [ Poupinet et al , 1984], a time delay between a signal pair is found from the linearity of the difference in their phase spectra. This approach can be improved considerably with the use of coherency‐based filtering [ Rowe et al , 2002]. …”
Section: Interstation Arrival Times: Vertical Componentsmentioning
confidence: 99%
“…Recent retrospective analyses of seismic data have taken advantage of waveform alignment and joint location methods to obtain remarkable improvements in the spatial clarity of event locations. Examples of such studies include Shearer [1997, 1998], Rubin et al [1999], Waldhauser et al [1999], Aster and Rowe [2000], Rowe et al [2002a, 2002b], Waldhauser and Ellsworth [2002], and Schaff et al [2002] for fault zones and Got et al [1994], Rubin et al [1998], Battaglia et al [2004], and Rowe et al [2004] for volcanoes. Waveform alignment reduces relative picking errors between earthquakes with similar waveforms, leading to higher‐precision differential times or absolute arrival time adjustments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accurate differential traveltimes obtained from seismic waveforms have been used to improve dramatically the relocation results for shallow crustal earthquakes (Got et al 1994; Dodge et al 1995; Shearer 1997; Rubin et al 1999; Waldhauser & Ellsworth 2000; Rowe et al 2002; Schaff et al 2002). Such studies often use a cross‐correlation (CC) technique to calculate the relative time delay between the waveforms of two events recorded at the same station to obtain sample‐level (sometimes even subsample‐level) relative pick accuracy.…”
Section: Introductionmentioning
confidence: 99%